2019
DOI: 10.1136/medethics-2019-105558
|View full text |Cite
|
Sign up to set email alerts
|

Betting on CPR: a modern version of Pascal’s Wager

Abstract: Many patients believe that cardiopulmonary resuscitation (CPR) is more likely to be successful than it really is in clinical practice. Even when working with accurate information, some nevertheless remain resolute in demanding maximal treatment. They maintain that even if survival after cardiac arrest with CPR is extremely low, the fact remains that it is still greater than the probability of survival after cardiac arrest without CPR (ie, zero). Without realising it, this line of reasoning is strikingly simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Resuscitate, intubate, hospitalize, operate, any treatment, etc.? Whether the decision is to stop all treatment or do maximal treatment (such as CPR), patients themselves may not understand the complexity of orders while they are dealing with the emotional component of a major decision [60]in those critical clinical moments. Thoroughly discussing the intensity of care and proposed interventions at the end-of-life are an important conversation to have with patients [61].…”
Section: Treatability Of Acute Medical Issuesmentioning
confidence: 99%
“…Resuscitate, intubate, hospitalize, operate, any treatment, etc.? Whether the decision is to stop all treatment or do maximal treatment (such as CPR), patients themselves may not understand the complexity of orders while they are dealing with the emotional component of a major decision [60]in those critical clinical moments. Thoroughly discussing the intensity of care and proposed interventions at the end-of-life are an important conversation to have with patients [61].…”
Section: Treatability Of Acute Medical Issuesmentioning
confidence: 99%
“…Others may base their decision on inaccurate assumptions. For instance, cardio-pulmonary resuscitation is not as successful as it is often perceived [20], so patients may overestimate its benefits and disregard its potential harms when taking their decision. Also, it has been shown that relatives acting as surrogate decision makers on life-sustaining treatment frequently feel overburdened [21] and make choices that often do not resonate with the patient's preferences [21,22].…”
Section: Decision Support?mentioning
confidence: 99%
“… 16 Meanwhile, many patients lack an advance directive or a surrogate who can decide for them, so strangers have to make the choices 17 ; Patients also have difficulties with planning their future care and understanding resuscitation scenarios, so they may not communicate their wishes or may have unrealistic expectations (eg, overestimating the success of cardio-pulmonary resuscitation). 18 Moreover, relatives who act as surrogates may experience stress and may not respect the patient's preferences. 19 These are only a few examples that demonstrate the need for novel approaches to decision making within the healthcare service delivery system.…”
Section: Introductionmentioning
confidence: 99%